METAPHORS OF THE HYPERMEDIATED CITY IN CONTEMPORARY ART (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The visualization of the informational dimension linked to the urban environment organizes a perception articulated through an ecosystem of screens from which the hypermediated city emerges. This article examines the impact of different artistic productions that, as metaphors of physical-digital reality, configure the phenomenology of the landscape disposed by the technological imperative.
Keywords: Metaphor; contemporary art; digital; hypermediated city; subjectivity